Research on the Influencing Factors of Women’s Willingness to Choose the Form of "Internet + Maternal and Child Health Care" for Pregnancy Health Care in Childbearing Age - Ma, Suxiang; Ren, Yuxuan; Xie, Shitong; Ding, Nan (Transactions on Economics, Business and Management Research, 2024)
Background: "Internet+Maternal and Child Health" platforms have been put into place, with women in childbearing age as the main audience. These platforms effectively protect mothers and children’s health and improve physicians’ performance. Nevertheless, the "Internet + maternal and child health" platforms have faded in the post-epidemic era, failing to meet the real needs of women who are pregnant. Methods: This paper takes the 1,608 data collected through the questionnaire survey as the research samples, and takes the basic information, medical background, health behaviour during pregnancy, needs during pregnancy and worries as the independent variables, and the willingness of women as the dependent variable, and explores the influence of different categories of independent variables on the dependent variables through Kendall’s tau correlation analysis, generalized linear model, and random forest regression model. Results: The platform is more likely to be used by higher income groups than lower income groups, and single and unmarried groups are more likely to use the platform than married and divorced groups. At the same time, the concerns and needs of women of the right age during pregnancy and childbearing are critical to the approval of the "Internet + Maternal and Child Health" platform. Conclusion: Women of the relevant age group should have their wants and concerns addressed via the "Internet+Maternal and Child Health" platform. Additionally, a comprehensive range of nanny services should be offered to enable women to obtain advice on healthy living during pregnancy.